PEMBERDAYAAN KADER PKK DAN PKD DALAM PENYEDIAAN MPASI SEHAT BERGIZI UNTUK MEWUJUDKAN PROGRAM ZERO STUNTING DI DESA KECAPI - Hamidaturrohmah, Hamidaturrohmah; Minardi, Joko; Adi Saputro, Yayan; Kartikasari, Fariza Yulia; Rizaldi, Muhammad Rifqi; Arianti, Dini; Ardiansyah, Ahamd Feri; Efendy, AH Surur (Jurnal Abdi Insani, 2024)
The stunting case in Kecapi Village is quite worrying so it requires collaboration and joint commitment that it can be handled comprehensively. Several main factors influence the occurrence high stunting in Kecapi village are 1) unbalanced nutritional intake; 2) birth weight does not meet standards; 3) Mother's education level is less than optimal; 4) careless environment for stunting cases. The aim this empowering is to increase the competence PKK and PKD partners in creating healthy, nutritious MPASI innovations as an effort to realize zero stunting. The method service activities using service learning includes the stages  socialization, training, mentoring, and reflective evaluation. Analyze partner needs through observation and interviews. The target activity was 40 PKK PKD cadres Kecapi village. The results this activity showed that was able to contribute to knowledge preventing stunting with result of 86%. This service program has positive effect on increasing skills and creativity partners in creating healthy, balanced nutritional food innovations used in preventing stunting with results of 83%. Third, this empowerment becomes support system for partners to be enthusiastic realizing zero stunting Kecapi village with an achievement of 85%. The benefits service activity can provide positive contribution to directly increasing the competence and skills partners.